Polystyrene nanoplastics promote colitis-associated cancer by disrupting lipid metabolism and inducing DNA damage - Shan Tian; Ruixue Li; Jiao Li; Jinhui Zou (Environment International)
Nanoplastics (NPs) have attracted widespread attention owing to their presence in the body. Recent studies highlighted the detrimental effects of NPs on the digestive tract. However, no studies have reported an association between NPs exposure and colitis-associated cancer (CAC). An azoxymethane/dextran sodium sulfate-induced CAC model was used, and polystyrene nanoparticles (PS-NPs) were selected for long-term exposure. Non-targeted metabolomics and 16S rRNA sequencing were used to detect changes in colonic metabolites and gut microbes following PS-NPs exposure. A lipopolysaccharide (LPS)-treated cancer cell model (Caco-2) exposed to PS-NPs was used to investigate the underlying molecular mechanism. Compared to the normal control group, mice in the PS-NPs group exhibited more tumor nodes and reactive oxygen species (ROS), higher expression of pan-CK and Ki-67, and more severe DNA damage. 16S rRNA sequencing revealed that exposure to PS-NPs altered the abundance of Allobaculum and Lactobacillus, whereas metabolic analysis showed that the most significant metabolites were enriched mostly in fatty acid metabolism. Experiments in LPS intervened Caco-2 cells showed that exposure to PS-NPs led to lipid peroxidation, oxidative stress, and DNA damage in Caco-2. Exposure to PS-NPs activated the phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathway both in the AOM/DSS mouse model and cellular model. Key proteins involved in fatty acid metabolism were downregulated in Caco-2 cells exposed to PS-NPs. The metabolic effects of cancer cells exposed to PS-NPs were significantly inhibited by the activation of the fatty acid metabolism pathway by fenofibrate. PS-NPs exposure disturbed lipid metabolism and induced DNA damage via the activation of PI3K/AKT/mTOR to promote CAC progression. Inhibition of fatty acid metabolism is a therapeutic target for controlling PS-NP-induced CAC. Our study provides an important reference for the prevention and treatment of CAC from the perspective of the environment and enhances awareness of the necessity of plastic control.